Design and Mechanism Analysis of Paddlewheel Aerator with Movable Blades. (May 2019) - Bahri, Samsul; Agus Setiawan, Radite Praeko; Hermawan, Wawan; Junior, Muhammad Zairin
Abstract: The successful of intensive aquaculture is strongly influenced by the ability of the farmers to overcome the deterioration of water quality. The problem is low dissolved oxygen through aeration process. The aerator device which widely used in pond farming is paddle wheel aerator because it is the best aerator in aeration mechanism and usable driven power. However, this aerator still has a low performance of aeration, so that the cost of aerator operational for aquaculture is still high. Up to now, the effort to improve the performance of aeration was done by two-dimensional blade design. Obviously, it does not provide an optimum result due to the power requirements for aeration is directly proportional to the increase of aeration rate. The development of movable blade is based on fact that power is required only when blade of paddle wheel aerator entering water and in contrary action of aeration effect only when the blade is about leaving the water. This study was carrier out to design paddle wheel aerator with movable blade which will open when entering water and close when leaving water. Wheel closed at quadrant I to IV (entering water surface) and was about to open at quadrant III to II (leaving water surface). The blade was designed referring to commonly used Taiwan wheel model. The size of the blade was 15 cm of width, 20 cm of length, trapezoid-shape with 15˚ of bottom side and 30˚ of top side, had 40 holes with diameter of 1.6 cm. The component of mobable blade mechanism consisted of cam and shaft, rim, rim cap, blade holder, follower, spring and bearing. Follower was able rotate with angle of rotation was 125 0, rotational displacement was 50 mm, maximum velocity was 0.55 m/s and acceleration was 6.09 m/s 2 . The largest angle of pressure occurred between cam and follower was 40.12 0 and the maximum torque required to rotate movable wheel was 80.09 Nm. The result shows that the testing without a load at 115 rpm, the torque that occured is 43.05 N·m and the electric power consumption is 511.72 Watt. However, the electrical consumption is still higher comparing with Taiwan paddlewheel aerator model due to the friction occured on the follower and cam.